Grandeur et décadence de l'appréhension psycho-artistique du dessin à l'école maternelle (1945-2013) - Ghislain Leroy
This article is a socio-historical study of designs of drawing in French preschool, from 1945 to 2013. Two documentary reviews were cross-referenced: the diachronic analysis of the professional journal « L'Éducation enfantine » and 125 inspection reports. Initially (1940s and 1950s), drawing generates more and more interest in this professional journal. It is considered as a way to penetrate the variety of child psychologies. This new approach progressively renders obsolete the old, more productive, less expressive conceptions of drawing. In the classes, little by little, it becomes highly legitimate, symbol of a preschool putting at the center a certain psychological and even artistic approach of the child. The question of the representation of the object became more and more secondary in the 1960s and free drawing spread into the classes. During the 1970s, other plastic arts activities competed with drawing in the expressive aims. Then, from the 1980s, until 2010, the criticism of libertarian pedagogies, then the scholification of French preschool, prolong the process of marginalization of the "expressive" drawing. All of those analysis inform on the evolution of the dominant representations of childhood in preschool and serves the socio-historical reflection on the links between art and school.